The impact of Non-performing Loans (NPL) towards profitability performance (ROA, ROE, & NPM) / Nor Farradila Abdul Aziz, Irwan Ibrahim and Maizura Isa @ Kamaruddin - Abdul Aziz, Nor Farradila; Ibrahim, Irwan; Isa @ Kamaruddin, Maizura (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2008)
In 1997, Asia witnessed the onset of one of the worst financial crises ever to hit the region. The Asian financial crisis swept the region when it was least expected and left seemingly irreparable effect on the economies. As financial intermediaries of the economy, the banking industry was significantly affected by the crisis. Non performing Loans (NPLs) began to rise as deteriorating finances of distressed borrowers and soaring interest rates impaired borrowers' ability to service loan. In addition, the collapse of financial and property asset values substantially reduced the value of the collateral for many bank loans. As a result, most financial institutions experienced erosion in profits. The financial institutions" capital base was affected by increased losses from loan defaults, requiring them to seek re-capitalization. Evaluation of bank performance is important for all parties including depositors, bank managers and regulators. This research focuses on the relationship between profitability performance including ROA, ROE and NPM against non performing loans (NPLs) and loan recovery income for four banks in Malaysia that have been selected as a sample. The purpose of this study is to identify which sector contributes to the largest portion in non performing loans (NPLs) and loan recovery income to profitability performance for each bank. There are few variables that have been used in this study. The dependent variables are non performing loans (NPLs) ratio and loan recovery income ratio whereas the independent variables are consists of return on assets (ROA), return on equity (ROE) and net profit margin (NPM). 2 local banks and 2 foreign banks in Malaysia have been chosen as a sample of data based on their equity and annual revenue. The data collections have been analyzed by using trend analysis and multiple regression analysis. The hypotheses have been developed and tested in order to decide whether there is a significant or insignificant relationship between NPLs and the profitability performance. From the analysis that has been done, it shows that financing to purchase residential property turned out as the largest contributor to non performing loans (NPLs). The test also indicates that there is a significant impact of NPLs to profitability performance for foreign banks whereas for local banks it depends on the individual bank. From the test also, it showed that there is no significant impact on loan recovery income towards profitability performance